Dengue Fever: An Emerging Infectious Disease in The Bahamas - Bain, Sherrie Valarie (International Journal of Bahamian Studies, 2011)
Dengue fever is an emerging infectious disease that is increasing in prevalence in many geographic regions, including the Caribbean. It is the most common arboviral (vector-borne) disease in the world, and infects more that 50 million people annually worldwide. The etiological agent of dengue fever is one of four serotypes of the Dengue virus (DENV1 – DENV4). The infection is transmitted via a human-mosquito-human route, when one or more species of the Aedes mosquito takes a blood meal from an infected host and then feeds on a person who is uninfected. There is no vaccine or cure for dengue fever. Dengue fever is a growing cause for concern in The Bahamas. This year the incidence of dengue fever reached epidemic proportions in The Bahamas. This article will explore the etiology and epidemiology of dengue fever, and offer some insight into how future the Bahamas can begin to develop strategies for the eradication of dengue fever.